THE IMPACT OF FLEXIBLE WORK POLICIES AND WORK-LIFE BALANCE ON EMPLOYEE PERFORMANCE (GRAB DRIVER CBD POLONIA) - Muhammad Zakiul Fuad Batubara; Nursakinah Ritonga; Lisa Iryani; Nursanjaya; Sufi (RADJA PUBLIKA, 2025)
The development of the modern workplace demands that companies create adaptive work systems, including through the implementation of flexible work policies and efforts to maintain a balance between work and personal life for employees. This study aims to determine the effect of flexible work policies and work-life balance on employee performance, specifically for Grab drivers in the Polonia CBD area. This study used a quantitative approach with data collection techniques through distributing questionnaires to respondents selected non-probabilistically. The data obtained were analyzed using multiple linear regression methods with the assistance of statistical software. The results showed that flexible work policies did not have a significant impact on individual employee performance. Conversely, work-life balance was proven to have a positive and significant impact on improving employee performance. Meanwhile, together, both variables made a significant contribution to employee performance. From these findings, it can be concluded that efforts to create a balance between work and personal life have a more significant impact on performance than simply providing flexibility in work. Therefore, companies are advised to integrate flexible work policies with employee welfare support programs to create a more productive and sustainable work environment.